2015
DOI: 10.1165/rcmb.2014-0327oc
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cell DNA Methyltransferase Inhibition Accelerates Resolution of Lung Inflammation

Abstract: Acute respiratory distress syndrome (ARDS) is a common and often fatal inflammatory lung condition without effective targeted therapies. Regulatory T cells (Tregs) resolve lung inflammation, but mechanisms that enhance Tregs to promote resolution of established damage remain unknown. DNA demethylation at the forkhead box protein 3 (Foxp3) locus and other key Treg loci typify the Treg lineage. To test how dynamic DNA demethylation affects lung injury resolution, we administered the DNA methyltransferase inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
93
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 49 publications
1
93
0
Order By: Relevance
“…7B). We used a lower LPS dose because diphtheria toxin-treated Foxp3 DTR mice have increased susceptibility to intratracheal LPS and achieved similar depletion in PBS-and IL-4-treated groups (Ͻ0.2% of all CD4 ϩ cells in spleen, lung, BAL) as before (52). Despite Treg absence, IL-4 therapy in Foxp3 DTR mice significantly increased weights (Fig.…”
Section: Foxp3mentioning
confidence: 92%
See 1 more Smart Citation
“…7B). We used a lower LPS dose because diphtheria toxin-treated Foxp3 DTR mice have increased susceptibility to intratracheal LPS and achieved similar depletion in PBS-and IL-4-treated groups (Ͻ0.2% of all CD4 ϩ cells in spleen, lung, BAL) as before (52). Despite Treg absence, IL-4 therapy in Foxp3 DTR mice significantly increased weights (Fig.…”
Section: Foxp3mentioning
confidence: 92%
“…Diphtheria toxin (lot no. 15043A1; List Biological Laboratories) was diluted in PBS and administered via intraperitoneal injection on days Ϫ2 (50 g/kg mouse) and Ϫ1 (10 g/kg) before intratracheal LPS, and on days ϩ1, ϩ3, and ϩ5 (10 g/kg) following intratracheal LPS as previously described (52). Clodronate liposomes (Cl 2MDP) or PBS liposomes (control) were prepared as previously described (55), followed by intravenous instillation after being diluted in 150 l of PBS on days 0 and ϩ3 relative to intratracheal LPS exposure.…”
Section: Methodsmentioning
confidence: 99%
“…We sought to support the notion that DNA methylation regulates cell phenotype in the pediatric E. coli LRTI model and measured the effect of pharmacologic disruption of DNA methylation on lung CD4 + T-cell markers. Administration of the DNA methyltransferase inhibitor decitabine (DAC) (14) for three daily doses starting 24 hours after low-dose (sub-lethal) E. coli or PBS aspiration led to changes in lung CD4 + Tcell phenotype that were more pronounced in neonates compared with juveniles. In neonates, dimensionality reduction using t-distributed stochastic neighbor embedding (tSNE) on the flow-cytometric cellular marker profile revealed differences associated with E. coli LRTI that were further modified by DAC administration (Fig.…”
Section: Disruption Of Dna Methylation Produces Lung Cd4mentioning
confidence: 99%
“…This skewed T-cell function renders neonates with an immature CD4 + T-cell response to bacterial infection, with hypofunctional Th1-and Th17-coordinated protection from microbial pathogens (13). CD4 + regulatory T (Treg) cells, which express the lineage-specifying transcription factor Foxp3, play a central role in providing tissue protection as well as orchestrating resolution and repair from lung inflammation and injury in adult (14)(15)(16) and neonatal (17) mice. Studies in murine systems demonstrated that heterochronic adoptive transfer of adult Treg cells to neonatal mice at the time of lipopolysaccharide-induced acute lung injury provided tissue protection and normal developmental weight gain within 48-72 hours compared to a sham administration of adult CD8…”
mentioning
confidence: 99%
“…This FDA-approved drug is used to treat myelodysplastic syndrome (30) and is also an effective therapy against some inflammatory disease models (31)(32)(33). The treatment has also been proposed to act by increasing the potency of the Treg response (32)(33)(34), and we further evaluate this notion using an infectious disease model of inflammation.…”
mentioning
confidence: 99%